Growing up social : raising relational kids in a screen-driven world - Chapman, Gary D., 1938- (Northfield Publishing, 2014)
"In this digital age, children are spending more and more time interacting with a screen rather than a parent. Technology has the potential to add value to our families, but it can also erode a sense of togetherness and hinder a child's emotional growth. In Growing Up Social: Raising Relational Kids in a Screen-Driven World, you'll learn how to take back your home from an over-dependence on screens. Discover the five A+ skills needed to give your child the relational edge in a screen-driven world: affection, appreciation, anger management, apology, and attention. Today's screens aren't just in our living rooms; they are in our pockets. Now is the time to equip your child to live with screen time, not for screen time. Constant entertainment is not the goal of childhood. No phone, tablet, or gaming device can teach your child how to have healthy relationships; only you can. Growing Up Social will help you: - Equip your child to be relational rich in a digital world - Replace mindless screen time with meaningful family time - Establish simple boundaries that make a huge difference - Read what's working for the screen savvy family down the street - Prepare your child to succeed down the road in relationships and life - Learn healthy ways to occupy your child while you get things done"--